Perlindungan Hukum Terhadap Konsumen Obat Terkait Hak Atas Informasi Dan Petunjuk Penggunaan Dalam Bahasa Indonesia Di Kota Medan - Zai, Kelvin Putra; Siregar, Taufik; Lubis, Mhd Ansor (JUNCTO: Jurnal Ilmiah Hukum, 2023)
Consumer Protection is all efforts to guarantee legal certainty to provide protection to consumers. For example, the circulation of drug products that do not include information and/or instructions for use in Indonesian, consumers may be disadvantaged if there is no complete and clear information on the drug labels. So that raises several questions about how the law regulates the circulation of drugs without a distribution permit, how are the legal arrangements for consumers regarding the right to information and instructions for using drugs in Indonesian and what are the legal responsibilities for distributing drugs without information and instructions for using Indonesian at the BPOM in Medan. The method used in this study is normative juridical, namely a research method that examines document studies, namely by using various data such as legislation, legal theory of court decisions. circulating in accordance with Law NO. 8 of 1999 concerning Consumer Protection, Article 8 paragraph 1 (j). The effectiveness of the government in supervising and implementing the rules that have been made is very necessary so that the law can work in accordance with the objectives of these laws and regulations, namely to protect the public from drug abuse as a result of the inclusion of inadequate information on drug use.